Effect of Preablation Glycemic Control on Outcomes of Atrial Fibrillation Patients With Diabetes Mellitus Following Valvular Surgery Combined With the Cox-Maze IV Procedure - Peng, Zhan; Zhao, Rui; Liu, Yuhua; Yang, Yunxiao; Yang, Xiubin; Hua, Kun (Frontiers in Cardiovascular Medicine, 2022)
Background This study was performed to assess the effect of preablation glycemic control on atrial fibrillation recurrence rates after heart valve surgery concomitant with Cox-Maze IV ablation. Methods Twelve-month preablation trends in glycemic control were studied. Recurrence and clinical outcome data were obtained during a mean follow-up period of 36.7 ± 23.3 months postablation. Results Higher glycated hemoglobin (HbA1c) at the time of ablation was associated with higher postablation recurrence rates. The cumulative atrial fibrillation recurrence-free survival of patients with HbA1c ≥7.5% at the time of operation at 12, 24, 36 and 48 months was 97.1, 78.3, 54.2, and 36.3%, respectively (P < 0.001), and 100, 84.9, 37.2, and 16.2% for patients who preoperatively had an upward trend in HbA1c, respectively (P < 0.001). Conclusion Maintaining a downward trend in HbA1c during the 12-month period before the operation and an HbA1c value < 7.5% at the time of the operation reduced the recurrence of AF among patients who underwent heart valve surgery concomitant with the Cox-Maze IV procedure.